Some theoretical problems suggested by the movements of interest rates, bond yields and stock prices in the United States since 1856 - Macaulay, Frederick Robertson (New York, National bureau of economic research, 1938)
The book explains the course of interest rates and bond yields in the United States over a long period with a view to ascertaining what statistical relations these rates and yields bear to one another.
obn 25/01/2019
Loans
Keywords: Finance; Business cycles; Index numbers (Economics)